Observation of a helium ion energy threshold for retention in tungsten exposed to hydrogen/helium mixture plasma. (16th August 2016) - Thompson, M.; Deslandes, A.; Morgan, T.W.; Elliman, R.G.; De Temmerman, G.; Kluth, P.; Riley, D.; Corr, C.S.
Abstract: Helium retention is measured in tungsten samples exposed to mixed H/He plasma in the Magnum-PSI linear plasma device. It is observed that there is very little He retention below helium ion impact energies of 9.0 ± 1.4 eV, indicating the existence of a potential barrier which must be overcome for implantation to occur. The helium retention in samples exposed to plasma at temperatures  >1000 K is strongly correlated with nano-bubble formation measured using grazing incidence small-angle x-ray scattering. The diameters of nano-bubbles were not found to increase with increasing helium concentration, indicating that additional helium must be accommodated by increasing the bubble concentration or an increase in bubble pressure. For some samples pre-irradiation with heavy ions of 2.0 MeV energy is investigated to simulate the effects of neutron damage. It is observed that nano-bubble sizes are comparable between samples pre-irradiated with heavy-ions, and those without heavy-ion pre-irradiation.